Association between vaginal washing and vaginal bacterial concentrations - Sabo, Michelle C. (PLoS One, 2019)
Vaginal washing is a common practice associated with adverse outcomes including bacterial vaginosis (BV) and HIV infection. Prior studies have not examined the associations between vaginal washing and individual vaginal bacteria, or whether these associations are independent of the effect of vaginal washing on BV. The purpose of this study was to characterize the association between vaginal washing and the presence and concentrations of vaginal bacteria associated with optimal and sub-optimal vaginal states. The analysis utilized data from participants in the placebo arm of the Preventing Vaginal Infections trial, which enrolled HIV-uninfected women from the United States and Kenya. Detection of bacterial taxa associated with BV was compared between visits with versus without reported vaginal washing. The effect of vaginal washing on a number of vaginal bacteria differed substantially (p<0.05) between the US and Kenya, so results were stratified by country. In US women, vaginal washing was associated with a significantly higher likelihood of detection of BV associated bacterium 1 (BVAB1) (relative risk [RR] 1.55, 95% confidence interval [CI] 1.15–2.09, p = 0.004), BVAB2 (RR 1.99, 95%CI 1.46–2.71, p<0.001), Mageeibacillus indolicus (RR 2.08, 95%CI 1.46–2.96, p<0.001), Atopobium vaginae (RR 1.34, 95%CI 1.13–1.59, p = 0.001), Leptotrichia/Sneathia species (RR 1.66, 95% CI 1.33–2.09, p<0.001), Megasphaera species (RR 1.78, 95%CI 1.34–2.37, p<0.001) and Gardnerella vaginalis (RR 1.08, 95%CI 1.01–1.16, p = 0.02). No significant association between vaginal washing and bacterial detection was found in Kenyan women. Adjustment for bacterial vaginosis diagnosed by Gram stain did not alter these results. This study provides evidence that the association between vaginal washing and detection of individual bacterial taxa can vary regionally. For some vaginal bacteria, the association with vaginal washing may be independent of the effect on Gram stain detection of BV. Larger prospective studies in diverse geographic settings should explore whether eliminating vaginal washing impacts the presence and concentrations of key vaginal bacteria.